Protein isolation from brown seaweed, Saccharina latissima, as part of an integrated bio-refinery - axelsson, john (My University, 2017)
Seaweed can be a promising alternative to meet the increasing demands for new sustainable protein sources. A few attempts to isolate proteins from seaweed using e.g. solubilization in water plus ammonium sulphate precipitation or solubilization in alkaline solution followed by isoelectric precipitation (pH-shift processing) have been carried out to date. However, effects of seaweed preservation technique and harvest season on the yield and quality of the protein recovered from seaweed have not earlier been studied. As part of the Swedish Seafarm project, cultivated Saccharina latissima harvested in May was here subjected to six different preservation methods; freezing at -20°C/-80°C, oven-drying, sun-drying, freeze-drying and ensilaging where after the pH-shift process with protein solubilization at pH 12 and protein precipitation at pH 2 (+/- freeze-thawing) was applied. Seasonality was studied only for the oven dried samples (harvest in March, April and May). Yield and quality of proteins in terms of nutritional, structural and techno-functional properties were followed. The freeze-dried biomass gave the highest protein yield, 11.2 %, closely followed by the -20°C frozen and oven-dried biomasses at 11.1 % and 10.0 %, respectively. The ensilaged, sun-dried and -80°C frozen biomasses reached significantly lower yields of 7.6 %, 7.4 % and 6.3 %, respectively. With freeze-thawingaided precipitation, there was a significant increase in protein yield for all biomasses, except the sun-dried. The freeze-dried, -20°C frozen, oven-dried, ensilaged, sun-dried and -80°C frozen biomasses achieved protein yields of 26.6 %, 19.9 %, 20.3 %, 11.7 %, 13.4 % and 19.8 %, respectively with this technique. Higher protein yield was obtained for the biomass harvested at March (18.7/30.4 % without/with freezethawing) compared to April (8.4/24.3 % without/with freeze-thawing) and May (10.0/20.3 % without/with freeze-thawing). The protein isolate produced from the freeze-dried biomass achieved the highest protein content, 28.0 % on dry matter basis, followed by the oven-dried, -20°C frozen, sun-dried, -80°C frozen and ensilaged biomasses at 24.9 %, 22.0 %, 15.4 %, 15.3 % and 1.3 %, respectively. However, the protein isolates produced with an extra freeze-thawing step during precipitation resulted in significantly different protein contents for the isolates from all biomasses, with isolates from the oven-dried, freeze-dried, -80°C frozen, sun-dried, -20°C frozen and ensilaged biomass containing 40.5 %, 37.6 %, 26.2 %, 20.3 %, 19.0 % and 2.0 % protein/dw, respectively. Compared to the initial biomasses these protein isolates, in most cases, were significantly upconcentrated in protein content, with the concentration factor being from 3 to 5. The protein isolates achieved a significant increase in essential amino acids (g EAA/ 100 g protein) compared to the initial biomass and met the FAO/WHO adult and infant daily intake recommendations for valine, threonine, isoleucine, leucine, lysine and phenylalanine, in most cases. Preservation method affected the amino acid patterns of the initial biomasses and their respective protein isolates. Total EAA content varied from ~40.2-47.3 g AA/ 100 g protein for the initial biomass, ~49.7-52.6 g AA/ 100 g protein for the protein isolate produced without a freeze-thawing step and ~47.7-52.6 g AA/ 100 g protein for the protein isolate produced with freeze-thawing-aided precipitation. Four of the differently preserved biomasses (-20°C frozen, sun-, oven- and freeze-dried) and their respective protein isolates were selected to be investigated further: As expected, the protein isolates displayed poor solubility in water at pH ~2, however, achieving great solubility at pH 7 (70-80 %) and pH 11 (80-100 %). For the protein isolate produced without freeze-thawing, there was little difference in protein solubility depending on storage treatment of the initial biomass, only the protein isolate produced from the sun-dried biomass had significantly higher protein solubility at pH 25. For the protein isolates produced with freeze-thawing, the protein isolates from the sun-dried and -20°C frozen biomasses again differed between pH 2-5, with high protein solubility. However, at higher pH, all isolates displayed a similar pattern.
Keywords: Biofysik; Livsmedelsteknik; Biophysics; Food Engineering